2013
DOI: 10.1002/art.38007
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐7 Enhances the Th1 Response to Promote the Development of Sjögren's Syndrome–like Autoimmune Exocrinopathy in Mice

Abstract: Objective Although elevated IL-7 levels were reported in patients with primary Sjӧgren’s syndrome (pSjS), the role of IL-7 in this disease remains unclear. Here we characterized the previously unexplored role of IL-7 in the development and onset of pSjS using C57BL/6.NOD-Aec1Aec2 (B6.NOD-Aec) mouse model that recapitulates human pSjS. Methods For gain-of-function studies, recombinant IL-7 or control PBS was injected intraperitoneally (i.p.) into 12-week old B6.NOD-Aec mice for 8 weeks. For loss-of-function s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 50 publications
2
52
1
Order By: Relevance
“…We found that IL-7 induced expansion of Th1/a2b1 + cells (50% of Th1 express a2b1 integrin versus 80% of Th17 that express a2b1) in the bone marrow, and the blocking anti-a2b1 integrin mAb reduced their numbers (26 versus 40% reduction of Th17 cells; data not shown). These results are in agreement with previous studies showing that IL-7 can also regulate Th1 cells (12,52), which also express a2b1 integrin, and collagen costimulates the production of IFN-g (53). In contrast, we have not detected Th1/Th17 cells in the bone marrow and these cells were not induced upon treatment with IL-7 (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…We found that IL-7 induced expansion of Th1/a2b1 + cells (50% of Th1 express a2b1 integrin versus 80% of Th17 that express a2b1) in the bone marrow, and the blocking anti-a2b1 integrin mAb reduced their numbers (26 versus 40% reduction of Th17 cells; data not shown). These results are in agreement with previous studies showing that IL-7 can also regulate Th1 cells (12,52), which also express a2b1 integrin, and collagen costimulates the production of IFN-g (53). In contrast, we have not detected Th1/Th17 cells in the bone marrow and these cells were not induced upon treatment with IL-7 (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, IL-7 induces proliferation of naive and memory T cells (15) and enhances effector T cell responses, preferentially T helper 1 (Th1) and Th17 responses (16-18). These functional effects of IL-7 on T cells make IL-7 a critical enhancer of protective immunity, as well as of autoimmunity and inflammation (16,17,19,20).In the case of bacterial infections, gastric tissue biopsy specimens from patients infected with Helicobacter pylori (21) or mice infected with Mycobacterium tuberculosis have increased expression of . In addition, administration of exogenous IL-7 enhanced the survival of M. tuberculosis-infected mice (23).…”
mentioning
confidence: 99%
“…Moreover, IL-7 supports CD4 ϩ lymphoid tissue inducer (LTi) cell survival and function (14). Furthermore, IL-7 induces proliferation of naive and memory T cells (15) and enhances effector T cell responses, preferentially T helper 1 (Th1) and Th17 responses (16)(17)(18). These functional effects of IL-7 on T cells make IL-7 a critical enhancer of protective immunity, as well as of autoimmunity and inflammation (16,17,19,20).…”
mentioning
confidence: 99%
“…12 Moreover, we have reported that endogenous and exogenous IL-7 enhances Th1 responses and plays an essential role in the development and onset of SS-like exocrinopathy of salivary glands. 13 These findings provide additional evidence for the pathologic consequences of excessive IL-7 production induced by innate immune signaling 14 that can facilitate the pathogenesis of development and onset of multiple autoimmune disorders, mainly by enhancing Th1 and T cytotoxic 1 (Tc1) immune responses in the target tissues. [15][16][17][18] The lacrimal gland (LAC) is a primary target organ affected by SS.…”
mentioning
confidence: 98%
“…To determine whether similar events are induced by poly I:C in the LAC, we pretreated C57BL/6 mice with an anti-IL-7Ra antibody, which competitively inhibits IL-7 binding to IL7Ra, 12,13 or its isotype control IgG before IP administration of poly I:C. Poly I:C treatment induced a considerable increase in the expression of all three CXCR3 ligands, CXCL9, 10, and 11, in the LAC, and this increase was dramatically reduced by anti-IL7Ra treatment ( Fig. 2A).…”
Section: Induction Of Cxcr3 Ligands In the Lac By Poly I:c And Il-7mentioning
confidence: 99%